The Relationships Between Technology Adoption, HR Competencies, and HR Analytics of Large-Size Enterprises - Sukawat Penpokai; Sujira Vuthisopon; Amnuay Saengnoree (My University, 2023)
Purpose: The aim of this study is to explore the organizational construct that have relationship to HR Analytics in large-size organizations that operate their businesses in Thailand. Theoretical framework: Technology Adoption and HR Competencies are the two organizational constructs that are introduced in this study to examine their relationship with the HR Analytics. Design/methodology/approach: The study adopts a confirmatory factor analysis to develop the structural equation model through data collection from large-size organizations in Thailand. Findings: The hypotheses of the proposed conceptual framework are confirmed at significant level of p < 0.01. In addition, the study also provided statistical confirmation of the role of Technology Adoption as a mediating factor of HR Competencies to HR Analytics. Research, Practical & Social implications: The study gives the results to support the call from many authors around the area of HR Analytics and its influence on organization management. Originality/value: The study offers pioneer views on the relationship of relevant organizational dimensions to the HR Analytics and helps to bridge the gaps on the existing studies.
Keywords: Bridge (graph theory); AI and HR Technologies